NASAL PREFIXES AS DENOMINAL VERB FORMERS IN JAVANESE LANGUAGE - Nanik Herawati; Dwi Bambang Putut Setiyadi (International Journal of Humanity Studies (IJHS), 2021)
This research focuses on nasal prefixes as denominal verb formers in Javanese language. The formulation of problem can be stated as follows: (1) how is the form of denominal verbs with nasal prefixes? (2) what is the function of nasal in the forming of denominal verbs? (3) what is the meaning of nasal prefixes in denominal verbs forming? The goal of this research is to describe the function of nasal in the forming of denominal verbs in Javanese language. Research methodology includes: research strategy, location of the research, data and the source, data collection technique, data analysis technique, and the analysis of the result. There are three results, they are: (1) the form of denominal verbs with nasal prefixes in Javanese language (2) the function of nasal in the forming of denominal verbs of Javanese language (3) the meanings of nasal prefixes in the forming of denominal verbs.